THE INFLUENCE OF DIFFERENCES IN SURIMI RAW MATERIALS ON THE SENSORY CHARACTERISTICS OF FISH DUMPLINGS - Halim, Arif Rahman (Politeknik Kelautan dan Perikanan Dumai, 2024)
Surimi is Japanese, meaning crushed meat. To encourage fish consumption, products made from processed surimi are made more varied and interesting, such as fish dumplings. This research aimed to determine the differences in the sensory characteristics of surimi from different raw materials (swangi fish, kurisi fish, and kuniran fish). Apart from that, we also want to know the organoleptic and hedonic test results of fish dumplings made from different surimi raw materials. The surimi testing method includes an appearance test, folding test, and bite test on three different types of surimi (SU1 = kurisi fish, SU2 = swangi fish, SU3 = kuniran fish). Organoleptic and hedonic test methods for fish dumplings include appearance, smell, taste, and texture. The research results showed that there was a significant difference in the physical test of surimi (fold and bite test), while in the appearance test, there was no real difference. The surimi organoleptic test showed that there was no difference in smell and taste, while there were different results in appearance and texture parameters. The results of the hedonic test showed that panelists preferred sample SU1 on appearance and smell parameters, SU2 was preferred on taste parameters, and SU3 was superior on texture parameters.